Delineating borders of urban activity zones with free-floating bike sharing spatial interaction network. (October 2022) - Chen, Wendong; Chen, Xuewu; Cheng, Long; Liu, Xize; Chen, Jingxu
Abstract: Free-floating bike sharing (FFBS) programs have been put into use in many cities around the world in an effort to provide travel convenience for local inhabitants. However, it is unclear whether the existing administrative subdivisions reflect the most plausible spatial structure for the daily movements of FFBS users. In this study, we first build a spatial interaction network based on FFBS journey data from Nanjing, China. On this basis, urban activity zones are delineated leveraging the Leiden community detection algorithm, and a set of network measures are then utilized to examine the properties of these activity zones. The community detection results show that the identified activity zone borders rarely overlap with existing administrative district borders. Activity zone borders could separate FFBS travel flows more rationally than administrative district borders. In order to quantitatively explore the attenuation effect of activity zone borders on FFBS travel flows, we further subdivide the borders into various types (i.e., administrative, natural, and infrastructural borders) and construct border effect models. The regression results show that, in addition to demographic size, built environment, and distance factors, the activity zone border parameters are also revealed as important predictors of bilateral travel flows. Among the different types of activity zone borders, natural borders consisting of water bodies and mountains have the most significant attenuation effect on FFBS travel flows. The delineation of activity zones could better portray short-distance mobility patterns and urban structures, thereby providing nuanced and appropriate guidance for deliberating related policies. Highlights: The activity zone borders are identified on the basis of the free-floating bike sharing (FFBS) spatial interaction network. The delineation of activity zones unveils well the mobility patterns of FFBS users within and between urban sub-regions. The activity zone borders overlap more with natural and infrastructural borders while less with administrative borders. Natural borders have a more pronounced attenuation effect on FFBS travel flows.